What Determines Patents per Capita in OECD Countries? - Martin Falk (Austrian Institute of Economic Research (WIFO), 2004)
This paper investigates the determinants of EPO (European Patent Office) patent applications per capita using a panel of 22 OECD countries with data measured as five-year averages for the period 1980-1999. The patent production function is specified as a partial adjustment model and is estimated using system and first-differenced GMM (generalised method of moments) estimators. Estimates using system GMM estimators show a moderate degree of persistence in EPO patents per capita with an adjustment rate of around 25 percent between the five-year averages. Specialization in information and communication technology (ICT) patents measured as the share of ICT patents in total patents has a significant and positive impact on EPO patents per capita. Business enterprise R&D (BERD) expenditures are more effective in generating patent applications than public sector R&D with long-run elasticities of 1.04 and 0.24, respectively. The remaining variables, such as the strength of patent protection, human capital intensity and GDP per capita, are significantly positively related to EPO patents per capita in the static panel data model but are no longer significantly positive in the dynamic panel data model. Openness is not significantly different from zero in most of the specifications. Finally, we do not find any impact of publicly financed industrial R&D on EPO patent applications per capita.
Keywords: O30; O31; O33; 330; knowledge production function; patents; R&D; ICT patents; panel data; Patent; Industrieforschung; Technologiepolitik; Patentrecht; Humankapital; Panel; OECD-Staaten